2005
DOI: 10.1016/j.jamda.2004.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Feeding tube use in Italian nursing homes: The role of cultural factors

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A small-scale study from Italy declared the prevalence of tube feeding to range between ! 2.0% up to 6.6% in a few nursing homes, but did not mention a mean or median prevalence [9] . On a global scale, there are several studies comparing the use and prevalence of tube feeding in nursing home residents with advanced dementia [24] , which unfortunately are not comparable to this study as our questionnaire was not restricted to residents with dementia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A small-scale study from Italy declared the prevalence of tube feeding to range between ! 2.0% up to 6.6% in a few nursing homes, but did not mention a mean or median prevalence [9] . On a global scale, there are several studies comparing the use and prevalence of tube feeding in nursing home residents with advanced dementia [24] , which unfortunately are not comparable to this study as our questionnaire was not restricted to residents with dementia.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, reliable data are lacking in Germany and other European countries regarding the prevalence and use of enteral feeding via PEG in nursing homes. Significant differences between countries are thought to exist [8,9] . PEG use in nursing homes is a field of high interest because critics of artificial nutrition in the elderly presume that this method is partly misused to ease care without any reasonable medical indication [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 5-30% of the advanced dementia patients in nursing homes are on tube feeding in Europe and the USA; whereas, in Japan, approximately 50% of those are on tube feeding. [3][4][5][6] Thus, the percentage of tube feeding including PEG for dementia patients is higher in Japan than that in Western countries. However, recent studies have questioned the appropriateness of tube feeding in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Likely, the reduced use of feeding tubes in Italian nursing homes is due to the lack of education in the field of artificial nutrition, in addition to financial and environment‐specific factors and cultural background. Indeed, the Italian attitude toward end‐of‐life decisions is certainly less aggressive than that of other countries (United States or Netherlands) 33 . Also in our study, feeding tubes have a limited use (an average of 6.6% of NHRs).…”
Section: Discussionmentioning
confidence: 51%
“…A French multicentric study observed a significantly less prevalent use compared with the United States 32 . Recently Bellelli et al 33 conducted 2 surveys at different times in 1 nursing home in the province of Brescia and in 31 nursing homes in the province of Cremona (Lombardia Region, Italy). They found that the use of EN was low among Italian NHRs (the global use of tube feeding varied from less than 2% to 6.6%), was significantly lower than in U.S. facilities, and was not associated with common clinical or nursing home's characteristics.…”
Section: Discussionmentioning
confidence: 99%